Incidence of SARS-CoV-2 infection in children shortly after ending zero-COVID-19 policy in China on December 7, 2022: a cross-sectional, multicenter, seroepidemiological study - Zhou, Yi-Hua; Xu, Chenyu; Tao, Yue; Gu, Meng; Zhou, Guiping; Zhou, Wei; Jin, Yue; Xie, Jun; Xu, Biyun; Zhou, Wensan; Chen, Junhao; Shi, Weifeng (Frontiers in Public Health, 2023)
Background China discontinued the zero-COVID-19 policy on December 7, 2022, and then COVID-19 surged mid-December 2022 through mid-January 2023. However, the actual incidence was unknown. This study aimed to estimate the incidence of SARS-CoV-2 infection in children shortly after ending the zero-COVID-19 policy. Methods This multicenter cross-sectional study included 1,065 children aged 8 months to 12 years from seven hospitals at six regions across Jiangsu province, based on the convenience sampling, from February 10 to March 10, 2023. Group I comprised 324 children aged 8 months–2 years without COVID-19 vaccination, group II consisted of 338 preschool children aged 3–5 years with varied vaccination history, and group III contained 403 primary school children aged 6–12 years with mostly vaccinated. The COVID-19 vaccines were composed of inactivated SARS-CoV-2. In addition, 96 children’s sera collected in 2014 were included as negative controls. IgG and IgM antibodies against nucleocapsid (N) and subunit 1 of spike (S1) of SARS-CoV-2 (anti-N/S1) were measured with commercial kits (YHLO Biotech, Shenzhen, China). Results None of the 96 children (5.1 ± 3.5 years; 58.3% boys) in 2014 was positive for anti-N/S1 IgG or IgM. Of the 1,065 children (5.0 ± 3.5 years; 56.0% boys), 988 (92.8%) were anti-N/S1 IgG positive but none was anti-N/S1 IgM positive. The positive rate of anti-N/S1 IgG in Group I, II, and III was 90.4, 88.5, and 98.3%, respectively, with significantly higher in group III than in groups I and II (p < 0.0001). The median antibody titers in group III (381.61 AU/ml) were much higher than that in group I (38.34 AU/ml) and II (51.88 AU/ml; p < 0.0001). Conclusion More than 90% children experienced SARS-CoV-2 infection shortly after ending zero-COVID-19 policy in China, much higher than estimated infections by other studies. The widespread SARS-CoV-2 infection in unvaccinated children should be influential on the policy of COVID-19 vaccination in children in the future.